A condição das coxas anteriores, do meso-catepímero e do meso-catepisterno dos Tabanidae (Diptera) e sua possível importância na classificação - Bernardi, Nelson [UNESP] (Sociedade Brasileira de Zoologia, 1990)
The condition of certain neglected structures and their possible importance to the classification of the family Tabanidae are studied. The front coxae are considered as belonging to two types: 1) short and robust; 2) long and slender. The posterior edge of the meso-katepimeron presents two conditions: 1) without projection, 2) with backward projection. Similar conditions are found in the meso-Katepisternum, but with intermediate conditions. These characters are discussed in relation to the system proposed for the family by Mackerras. Conditions 1 and 2 of the former two structures separate, respectively, the Pangoniinae and Scepsidinae from the Chrysopsinae and Tabaninae. Condition 2 of the third structure seems to be developing independently in different groups of Tabaninae, with varying degrees of development.